Analysis of the Changes in State Budget Transfer Funds Policy from Central Government to Local Government - Galura Teja Utama, Raden; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2017)
Abstract. In accordance to Law No. 23/2014, the energy development are also responsibility of the Local Governments, but, the Central Government still have to intervene funding through the Special Allocation Fund (DAK) since 2011. In 2016 changes made to the mechanisms in the preparation of DAK allocation, where previously based on the calculation from Central Government (Formula Base) became based on the proposals from Local Government (Proposal Base). So, it is necessary to analyze impact from that changes and develop policies to response. This research was conducted by using “policy analysis”, “system thinking” and “CATWOE Analysis”And the result are: (i) the policy problem are the good proposal dominated from no DAK priority locations, Issue related to political aspect, Possibility an intervention; (ii) the policy performance are Local Governments not able to absorb DAK allocation maximally; (iii) the policy futures are Local governments expected can show their independence by developing the energy sector using Local Government budget, so the MEMR responsibility only as an energy sector regulator; (iv) the policy action are maximize the role of MEMR unit such as R & D MEMR, HRDA MEMR and DG EBTKE; (v) the policy outcomes  is Improve the renewable energy composition in the energy mix, and for the alternative policy is to Establish a non-structural Institution and the duties are to collect funds from funding agencies and doing coordinate cross-institutional and local government to build renewable energy.Keywords Energy Policy, the Special Allocation Fund (DAK), Autonomous Region, Policy Analysis, Systems Thinking